Prevalence and characterization of extended‐spectrum β‐lactamase‐producing clinical Salmonella enterica isolates in Dakar, Senegal, from 1999 to 2009. (30th August 2013) - Harrois, D.; Breurec, S.; Seck, A.; Delauné, A.; Le Hello, S.; Pardos de la Gándara, M.; Sontag, L.; Perrier‐Gros‐Claude, J.‐D.; Sire, J.‐M.; Garin, B.; Weill, F.‐X.; Cantón, R.
Abstract A total of 1623 clinical isolates of Salmonella belonging to 229 serotypes were received by the Senegalese Reference Center for Enterobacteria from January 1999 to December 2009. The most common serotypes were Enteritidis (19% of the isolates), Typhi (8%), Typhimurium (7%) and Kentucky (4%). A significant increase in the prevalence of resistance to amoxicillin (0.9% in 1999 to 11.1% in 2009) and nalidixic acid (0.9% in 1999 to 26.7% in 2009) was observed in non‐typhoidal Salmonella serotypes. For critically important antibiotics, notably ciprofloxacin and extended‐spectrum cephalosporins (ESCs), the rates of resistance were low: 0.3% and 0.5%, respectively. Seven ESC‐resistant Salmonella strains and three additional ESC‐resistant strains from Senegal (1990) and Mali (2007) were studied to identify the genetic basis of their antibiotic resistance. All ESC‐resistant strains produced an extended‐spectrum β‐lactamase (ESBL). These were CTX‐M‐15 (n = 6; 2000–2008), SHV‐12 (n = 3; 2000–2001) and SHV‐2 (n = 1; 1990). A large IncHI2 ST1 pK29‐like plasmid was found in six strains (three producing SHV‐12 and three CTX‐M‐15), whereas IncN and IncF plasmids were found in three strains and one strain, respectively. The association of plasmid‐mediated quinolone resistance (PMQR) genes qnrB1 and aac(6′)‐Ib‐cr was found in four ESBL‐producing strains, leading to decreased susceptibility and even full resistance to ciprofloxacin (MIC range 0.75–2 mg/L) despite the absence of mutations in the quinolone resistance‐determining region (QRDR) of gyrA, gyrB, parC and parE. This association of ESBL and multiple PMQR mechanisms within the same strains is therefore a serious concern as it hampers the use of both ESCs and fluoroquinolones for severe Salmonella infections.